If you think the limit does not exist, submit your answer as 0.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Express the given limit as x → ∞ lim x ( ln ( x ) ) 3 1 + x → ∞ lim ( ln ( x ) ) 3 1 + x → ∞ lim ( ln ( x ) ) 3 x
Since lim x → ∞ x ( ln ( x ) ) 3 = ∞ and lim x → ∞ ( ln ( x ) ) 3 = ∞ , x → ∞ lim x ( ln ( x ) ) 3 1 = 0 and x → ∞ lim ( ln ( x ) ) 3 1 = 0 We then evaluate x → ∞ lim ( ln ( x ) ) 3 x There are few ways to evaluate the limit.
L'Hôpital's Rule
Since lim x → ∞ x = ∞ and lim x → ∞ ( ln ( x ) ) 3 = ∞ , which leads to indeterminate form ∞ / ∞ , by L'Hôpital's Rule , lim x → ∞ d x d ( ( ln ( x ) ) 3 ) d x d ( x ) = lim x → ∞ x 3 ln 2 ( x ) 1 = lim x → ∞ 3 ln 2 ( x ) x = 3 1 lim x → ∞ ln 2 ( x ) x By the same reason, 3 1 lim x → ∞ ln 2 ( x ) x = 3 1 lim x → ∞ x 2 ln ( x ) 1 = 6 1 lim x → ∞ ln ( x ) x = 6 1 lim x → ∞ x 1 1 = 6 1 lim x → ∞ x = ∞
Logarithm Trick
Instead of L'Hôpital's Rule, we can evaluate the limit by ln i.e. y ln ( y ) = lim x → ∞ ln 3 ( x ) x = lim x → ∞ ln ( ln 3 ( x ) x ) = lim x → ∞ ln ( x ) − 3 lim x → ∞ ln ( ln ( x ) ) = lim x → ∞ ln ( x ) + 0 = lim x → ∞ ln ( x ) Since lim x → ∞ ln ( x ) = ∞ , y = ∞ , which proves that limit does not exist .